Optimalisasi Persediaan Bahan Baku di PT. ABC Menggunakan Metode Economic Order Quantity (EOQ) dan Reorder Point (ROP) - Aditya Trisna Putra; Dimas Nugroho Dwi Seputro (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Manufacturing companies frequently encounter inventory management problems that lead to excessive storage costs or raw material shortages, which can disrupt production activities. PT. ABC, a wood-processing manufacturing company, faces similar challenges due to the variety of raw materials used and the absence of optimal inventory control calculations. This study aims to optimize raw material inventory management at PT. ABC by applying the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods in order to minimize total inventory costs and prevent stock shortages. The research adopts a descriptive quantitative approach using historical data on demand, ordering costs, holding costs, and lead time over a four-month period. EOQ analysis is employed to determine the optimal order quantity, while ROP is calculated to establish an appropriate reorder point. The results show that the optimal order quantity for masker raw materials is 49 packs per order with a minimum total inventory cost of IDR 55,889, while plastic film has an optimal order quantity of 16 units per order with a minimum total inventory cost of IDR 177,146. The application of EOQ and ROP proves effective in reducing inventory costs and ensuring production continuity. These findings provide practical recommendations for improving inventory efficiency and supporting sustainable operational performance at PT. ABC.